2021
DOI: 10.5021/ad.2021.33.5.402
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 7 (TLR7) Mediated Transcriptomic Changes on Human Mast Cells

Abstract: Background Mast cells are skin immune sentinels located in the upper dermis, where wheal formation and sensory nerve stimulation take place. Skin inflammation is occasionally accompanied by mast cell-driven responses with wheals, angioedema, or both. Immunoglobulin E (IgE) antibodies are regarded as typical stimuli to drive mast cell activation. However, various causative factors, including microbial infections, can drive IgE-independent mast cell response. When infected, the innate immunity orche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…For example, Castoldi et al demonstrated that lipopolysaccharide (LPS) triggered‐triacylglycerol synthesis is essential for inflammatory responses in macrophages (Castoldi et al, 2020). Cho et al reported that TLR7 activation is related with lipid droplet biogenesis in mast cells (Cho et al, 2021). While it is well‐accepted that TLRs are involved in modulating lipid homeostasis in immune cells (Jarc & Petan, 2020; Pereira‐Dutra et al, 2019), it is only recently shown that TLRs may also regulate lipid metabolism in other types of cells, such as liver cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Castoldi et al demonstrated that lipopolysaccharide (LPS) triggered‐triacylglycerol synthesis is essential for inflammatory responses in macrophages (Castoldi et al, 2020). Cho et al reported that TLR7 activation is related with lipid droplet biogenesis in mast cells (Cho et al, 2021). While it is well‐accepted that TLRs are involved in modulating lipid homeostasis in immune cells (Jarc & Petan, 2020; Pereira‐Dutra et al, 2019), it is only recently shown that TLRs may also regulate lipid metabolism in other types of cells, such as liver cells.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Castoldi et al demonstrated that lipopolysaccharide (LPS) triggered-triacylglycerol synthesis is essential for inflammatory responses in macrophages (Castoldi et al, 2020). Cho et al reported that TLR7 activation is related with lipid droplet biogenesis in mast cells (Cho et al, 2021).…”
mentioning
confidence: 99%
“…The total mapped read numbers were determined and normalized to detect the number of fragments per kilobase of transcript per million mapped reads and transcripts per kilobase. Differentially expressed gene analysis was performed using these values [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%